Axiomatic Design for Redesign of the Mucuna Slicing Machine - Febrina Agusti; Ringgo Ismoyo Buwono; Pitoyo Amrih; Damara Jibran Novianto; Adit Tri Wahyono; Winda Indriyani (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Machine redesign was now very important to solve existing design problems and adapt production flows to the development of industrial needs. One of the medium-sized industries that uses machines for its production is the Tempe Chips Industrial Center located in Grobog Village, Wonogiri District. The slicing machine currently used by the Tempe Chips Industrial Center located in Grobog Village, Wonogiri District often produces unstable cuts and a lot of waste. This study aims to present the Axiomatic Design (AD) model as a structured framework for redesigning a high-quality slicing machine. The Axiomatic Design method was used to translate customer needs (Voice of Customer) and environmental criteria (Voice of Environment) into Functional Requirements (FRs). FRs were then used as the main input in developing Design Parameters (DPs), resulting in a Design Matrix. The design results that the proposed design has two blades with a thickness of 2 mm, a 1/4 Hp dynamo, which requires an adjustment to the target capacity of ±10 kg/hour, dimensions of machine had 300 mm in length, 250 mm in width, and 399 mm in height. Axiomatic Design can be effectively applied as a framework for redesigning medium-scale industrial food processing machines, especially for Mucuna commodities, a relatively hard commodity that demands cutting precision. Further research was recommended to develop this design result to the detailed design and prototyping stage.